Correlations and coherence of monopolar EMG-currents of the medial gastrocnemius muscle in proximal and distal compartments - von Tscharner, Vinzenz; Maurer, Christian; Nigg, Benno M. (Frontiers in Physiology, 2014)
The penniform gastrocnemius muscle contains multiple heads in the proximal regions and the aponeuroses are attached to the Achilles tendon. The multiple head structure lead to the assumption that different regions of the muscle must be activated compartment wise. The purpose of this study was to compare the correlation and coherence of EMG-currents within and between proximal and distal compartments of the medial gastrocnemius muscle, which reflect underling synchronization of motor units. It was hypothesized and shown that phase-inverted signals represent a property that discriminates compartments. However, the phase-inverted and non-inverted signals showed values of correlations that were indicative for highly synchronized signals. The correlation increased with the complexity of the task and was higher for the calf-rising movement than while balancing in a tiptoe position. Because the muscle fibers do not span the whole length of the muscles one has to conclude that the MUs were synchronized by synchronizing the various motor nerves. This study shows that it is essential to measure monopolar signals and use non-isometric contractions to observe synchronization of the EMG-signals. One could speculate that compartmental differences can only be observed if more complex movements that generate rotational forces at the knee or ankle are used.